2018
DOI: 10.1159/000487479
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Prediction Role of Preoperative Serum Albumin Level in Patients with Intahepatic Cholangiocarcinoma Following Hepatectomy

Abstract: Background: There is little information regarding the role of preoperative serum albumin (ALB) in intrahepatic cholangiocarcinoma (ICC) patients who underwent liver resection. Methods: Clinicopathological characteristics and survival rate of 91 ICC patients who underwent surgery between 2009 and 2013 were included in this study. The optimal cut-off for ALB were determined by plotting the receiver operating characteristics curves of ALB in predicting overall survival (OS) and utilizing the Youden index. Long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…Thus, high PLR is associated with poor prognosis in various cancers, including the ICC in the present study [23,35]. It has been reported that the ALB level might correlate with the systemic in ammation [27]. Besides, the ALB is commonly used as the marker for assessing patient's nutritional status [27].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Thus, high PLR is associated with poor prognosis in various cancers, including the ICC in the present study [23,35]. It has been reported that the ALB level might correlate with the systemic in ammation [27]. Besides, the ALB is commonly used as the marker for assessing patient's nutritional status [27].…”
Section: Discussionmentioning
confidence: 60%
“…Chen and colleagues have reported that the PLR was an independent adverse prognostic factor for survival of ICC [13,23,25]. The ALB have been widely reported to be associated with the long-term outcomes of various cancers, including ICC [26,27]. In ammation-based scores consisting of CRP and ALB as the Glasgow prognostic score have been proven to be signi cantly associated with survival in various cancers [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several previous studies have reported the relationship between the PLR and hepato-pancreatico-biliary malignancies, only Chen and colleagues have reported that the PLR was an independent adverse prognostic factor for survival of ICC [13,24,28]. The ALB has been widely reported to be associated with the long-term outcomes of various cancers, including ICC [29,30]. In ammation-based scores consisting of CRP and ALB as the Glasgow prognostic score have been proven to be signi cantly associated with survival in various cancers [31,32].…”
Section: Discussionmentioning
confidence: 99%